Information systems architecture and technology. proceedings of 37th International Conference on Information Systems Architecture and Technology, ISAT 2016 /: proceedings of 37th International Conference on Information Systems Architecture and Technology, ISAT 2016. Part IV : ([2017]) - Unknown
No abstract available